Studi Komparasi Konsep Jubata dan YHWH dalam Keluaran 3:14 Sebagai Upaya Kontekstualisasi Berita Injil Bagi Suku Dayak Kanayatn - Andre David; Firman Panjaitan (SANCTUM DOMINE: JURNAL TEOLOGI, 2021)
The church in Indonesia is still struggling with contextualization effort that are able to land the understanding of Biblical Theology into the understanding of the local community. This happened because the church’s attitude tended to reject local wisdom and force western culture into the context of Indonesia Culture, especially the Kanayatn Dayak Culture. Several previous studies have tried to see how the Kanayatn Dayak tribe understand their faith in Jubata which is reflected in their local wisdom. However, these studied have no yet reach an attempt to estabilish Jubata’s identity as Yahweh. Therefore this article seeks to show that Jubata is Yahweh who has previously revealed himself to Israel, to build a contextual theology capable of transforming culture and the church, using qualitative research methods of ethnographic studies to examine to the local wisdom of the Kanayatn Dayak tribe and Intepretation textual to see how Yahweh existed in Exodus 3:14. The values of chirst must renew the local wisdom of the Dayak Kanayatn tribe and Jubata must be understood not as idols but as Yahweh who has sovereignty over the universe in the local wisdom version Dayak Kanayatn tribe. Because Jubata is Yahweh who has revealed himself with the phrase “I AM THAT I AM” to declare His eternal and sovereign existence to reveal himself to all mandkind, especially Dayak Kanayatn tribe.